Is entrepreneurship career goal among youth? An analytical study on institutional and policy expectations of youth - Dambugolla, D.W.C.P. (University of Jaffna, 2020)
Many countries of the world, developed and developing, are trying to foster entrepreneurship to accelerate the rural economy. However, there has been no systematic attempt to view this by young people as the goal of their careers. The main objective of this study was to examine the policies of entrepreneurship education and the dimensions of institutional support regarding the expectations of the entrepreneur in choosing entrepreneurship as his career goal about the youth sector. For this study, 70 registered young businessmen from 10 different sectors of the Ministry of Technology and Research (MTR) VIDATHA program were identified in 2012. Primary data was collected directly from young people through a questionnaire. The regression model was used to predict the level of entrepreneurial expectations of youngers as a dependent variable. The independent variables were categorized based on the criteria of entrepreneurship policy (the importance of policies, effectiveness, efficiency, and sustainability) and institutional support standards (entrepreneurial culture, education, business development support, and access to finance). The results of the study indicate that promoting the culture of entrepreneurship and business development support services were essential factors in the expectations of young entrepreneurs for institutional support and that the efficiency of policy is a crucial unique factor in predicting the entrepreneurial aspirations of youth in the field of entrepreneurship Policy. The main challenge for young entrepreneurs is to transform their business into a competitive and commercially viable business. Entrepreneurial education projects also have different goals and objectives depending on the target group, political agenda and types of interventions. Also, there is no single policy model to foster and encourage entrepreneurship among young people. Therefore, it is recommended to create a unique institutional framework to promote entrepreneurship amongst youth and suggest a formulate single policy model for promoting entrepreneurial activities among youth and the established key agency for coordinating of all sectors.
Keywords: Career option; Entrepreneurship development; Entrepreneurship policy; Institutional support and youth entrepreneurship